Pre-release diet effect on field survival and dispersal of Anastrepha ludens and Anastrepha obliqua (Diptera: Tephritidae) - Utgés, María Eugenia (2013)
The effect of pre-release diets on starvation resistance, field survival and dispersal of sterile Anastrepha ludens and Anastrepha obliqua fruit flies was investigated. Protein-enriched diets resulted in reduced longevity under laboratory and field conditions. Flies exposed to a combination of sugar and fresh mango fruit pulp showed greater longevity and field survival. Release–recapture experiments showed that this mango plus sugar diet resulted in the greatest trap capture and the longest life expectancy when compared with the other treatments. Per cent recapture ranged from 0.24% to 17.50%. More females than males were recaptured. Spatial distribution was not affected by diet treatment, sex or replicate, but was affected by environmental conditions, such as vegetation cover or shade in the case of A. ludens or prevalent winds in the case of A. obliqua. Our results confirm the trade-offs between better mating performance and reduced survival produced by protein-rich diets and suggest fresh mango fruits, their products or derivates as an alternative to be developed to overcome this problem for sterile insect technique programmes.